Self-regulation in South Africa's wireless application service provider industry. - Thusi, Nomsa (My University, 2017)
This research report reviews self-regulation in the WASP industry of South Africa. The Wireless Application Service Providers (WASP) industry comprises small and medium enterprises that offer wireless services to customers. Business offers include location-based services such as mobile payment services, tracking, traffic and emergency response services. Consumer offers include the provision of mobile content which comprises of services such as games, music and wallpapers to name but a few. The WASP industry is self-regulated and over the years, the WASP consumer business has lost credibility, since many customers are dissatisfied with services provided by some WASPs. Although there are WASPs that are ethical and exercise good practice, there are others that solely intend to engage in rogue activities to the detriment of unsuspecting victims. Examples of malpractices include subscribing customers to WASP services without their consent, false or misleading advertising, sending unsolicited messages and failure to cancel unwanted services. This research report reviews self-regulation in the WASP industry of South Africa. The impact of policies implemented by the WASP’s self-regulatory body, Wireless Application Service Providers Association (WASPA) is analysed. This study is quantitative and findings are based on empirical analysis of WASPA’s official records. Data was extracted from the WASPA adjudication archive and evaluated using ANOVA to test the hypothesis that WASPA policies have no impact in the number of customer care complaints. Research findings indicate that we can confidently reject the null hypothesis as there are variances in the levels of customer complaints. However, these variances may not necessarily due to WASPA policies; as established from the data trend analysis, significant decreases in the number of customer complaints are evident after the network operators have implemented the double opt-in mechanism to help protect customers from auto subscriptions
MBA Thesis
Keywords: WASP, WASPA, self-regulation